MENINGKATKAN HASIL BELAJAR PAK SISWA KELAS XI A2 DENGAN MENGGUNAKAN MODEL PEMBELAJARAN LEARNING TOGETHER - Hendrijeti Titaley (Institut Agama Kristen Negeri (IAKN) Ambon, 2020)
Abstract:Teachers who conduct Â Class Action Research are the right solution to improve the quality of learning in the classroom and reform in teaching more professional teachers to need to update learning. The reforms meant here are about conventional teaching methods becoming innovation.Regarding the above problems, it requires special skills from teachers to use various innovative teaching approaches. To find out the effectiveness of these various learning models, the teacher must take an action called CAR in the classroom to improve the quality of teacher teaching.After taking action in class, namely doing PTK in class to class XI A2 students at SMK Negeri 1 Ambon in improving student learning outcomes by using the Learning Together Learning Model seen in Cycle I which was carried out in class 9 students (34.62%) obtained PAK learning outcomes scores are below the average, 8 students (30.77%) are on average, and 9 others (34.62%) are above average, while learning is done using the visual image method. In Cycle II, 9 people (34.62%) obtained PAK learning outcomes below the average, 10 students (38.46%) were on the average, and 7 others (26.92%) were above average.Keywords: Learning outcomes PA, learning together learning modelÂ